2018
DOI: 10.1182/blood-2018-04-841585
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia downregulates protein S expression

Abstract: siblings were predicted to carry 2 mutant TMPRSS6 alleles. Thus, in many cases, it is highly likely that clinically affected individuals with 1 TMPRSS6 pathogenic variant possess a second occult mutant allele. While this manuscript was in preparation, another group of investigators also studied the utility of normalizing plasma hepcidin to the TfSat in patients with IRIDA. 6 In particular, they compared the TfSat:hepcidin ratio in TMPRSS6-mutated patients who had 1 or 2 mutated alleles and found that, in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 23 publications
1
60
0
1
Order By: Relevance
“…Hypoxia, obviously present in the COVID19 disease, is "per se" an important thrombogenic factor: examples of this pro-thrombotic effect are, for instance, sickle cell anemia, and high-altitude thrombosis. A reduced synthesis and release of the physiologic anticoagulant Protein S in hypoxic status, has been described as a possible cause of thrombosis [19].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Hypoxia, obviously present in the COVID19 disease, is "per se" an important thrombogenic factor: examples of this pro-thrombotic effect are, for instance, sickle cell anemia, and high-altitude thrombosis. A reduced synthesis and release of the physiologic anticoagulant Protein S in hypoxic status, has been described as a possible cause of thrombosis [19].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Our past studies [ 9 – 13 ] with the natural anticoagulant Protein S illuminated our understanding about the significance of Protein S -Factor IXa interaction in hemostasis. Further, we identified a critical role of Protein S in regulating hypoxia and associated thrombotic complications [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overlooked aspect of hypoxia and the IL6-induced cytokine storm is that both factors downregulate a key anticoagulant, Protein S [ 9 , 32 ] ( Figure 1 ). For example, in a population of stroke patients, IL6 was upregulated, and it caused downregulation of Protein S that resulted in venous thrombosis [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…46 In the present study, relative deficiencies in protein C, protein S, and AT were also observed in HAPs and SLPs, which, again is in accordance with earlier reports suggesting a higher prevalence of protein S deficiency in Asian populations compared with other risk factors, such as protein C and AT. [47][48][49][50] However, our study demonstrated greater protein S deficiency in HAPs compared with SLPs. This was in accordance with a report of protein S deficiency in an animal model resulting from hypoxia exposure.…”
Section: Discussionmentioning
confidence: 95%
“…This was in accordance with a report of protein S deficiency in an animal model resulting from hypoxia exposure. 50 Furthermore, AT deficiency leads to inhibition of prostacyclin release from endothelial cells, leading to platelet activation and aggregation and neutrophil tethering to blood vessels, and it increases the production of various cytokines and chemokines from endothelial cells. 51 Our study also revealed enhanced platelet and endothelial cell activation at HA.…”
Section: Discussionmentioning
confidence: 99%